Navigating Access and Optimizing Medication Infusions in an Academic Medical Center: A Quality Improvement Study - Herolind Jusufi; Nicholas Boivin (MDPI AG, 2023)
(1) Background: The rising prices of medical infusions have resulted in the increased utilization of policies for payors to manage costs. These policies can be disruptive to the continuity of care, and health systems should develop a systematic strategy to address market changes and prevent patient leakage. (2) Methods: A quality improvement study was conducted by an interdisciplinary workstream to assess the current state of infusion services in an academic medical center in the Midwest and to provide recommendations for immediate access improvement and long-term system planning. An organizational assessment of the value stream was completed, which analyzed the available infusion capacity, billing strategy, patient mix/volumes, payor mix, staffing levels, and current policies. The interventions implemented after developing the infusion system strategy were triaging patients to the appropriate site of care to increase infusion capacity and eliminating paper orders in one of the health system's Infusion Centers. (3) Results: Patients receiving medical infusions for oncologic conditions warrant unique considerations in evaluating the Infusion Center's efficiency due to the infusion regimen's length, complexity, and tolerability. The management of the payor site of care also poses a challenge for health systems to triage patients effectively without fragmenting care. (4) Conclusions: An organizational strategy around infusion services must include broad stakeholder representation to address the clinical, operational, and financial challenges to provide timely care to patients.